Implementation of an integrated care strategy for child contacts of tuberculosis patients: a quasi-experimental study protocol - Dione Benjumea-Bedoya; Esteban Villegas Arbeláez; Daniela Martínez-Peñaloza; Claudia Patricia Beltrán-Arroyave; Andrea Victoria Restrepo Gouzy; Diana Marín; Lina Marcela Cadavid Álvarez; Beatriz Molinares; Fernando Nicolás Montes Zuluaga; Henry Pulido Duarte; Pedro Mauricio Suárez Parra; Juan Carlos Alzate Ángel; et al. (BMC, 2023)
Abstract Background Childhood tuberculosis continues to be a major public health problem. Although the visibility of the epidemic in this population group has increased, further research is needed. Objective To design, implement and evaluate an integrated care strategy for children under five years old who are household contacts of bacteriologically confirmed pulmonary tuberculosis patients in Medellín and the Metropolitan Area. Methods A quasi-experimental study in which approximately 300 children who are household contacts of bacteriologically confirmed pulmonary tuberculosis patients from Medellín and the Metropolitan Area will be evaluated and recruited over one year. A subgroup of these children, estimated at 85, who require treatment for latent tuberculosis, will receive an integrated care strategy that includes: some modifications of the current standardized scheme in Colombia, with rifampicin treatment daily for four months, follow-up under the project scheme with nursing personnel, general practitioners, specialists, professionals from other disciplines such as social work, psychology, and nutritionist. Additionally, transportation and food assistance will be provided to encourage treatment compliance. This strategy will be compared with isoniazid treatment received by a cohort of children between 2015 and 2018 following the standardized scheme in the country. The study was approved by the CIB Research Ethics Committee and UPB. ClinicalTrials.gov identifier NCT04331262. Discussion This study is expected to contribute to the development of integrated care strategies for the treatment of latent tuberculosis in children. The results will have a direct impact on the management of childhood tuberculosis contributing to achieving the goals proposed by the World Health Organization's End TB Strategy. Trial registration ClinicalTrials.gov identifier NCT04331262 . Implementation of an Integrated Care Strategy for Children Contacts of Patients with Tuberculosis. Registered 2 April 2020.